How To Develop Kampung Wisata Batik Pesindon As A Tourist Destination In Pekalongan Through SWOT Analysis - Suprina, Rina; Nathania, Agrifina Amanda (Jurnal Penelitian Pariwisata, 2018)
Kampung Wisata Batik Pesindon (KWBP) is one of tourist destinations in Pekalongan, Indonesia, where people can find various products related to Batik. Although this area has been declared as a tourism village, it has been well known by tourists as there are not many tourists interested to come to this area. This study aims to determine the strategy that can be applied to develop Kampoeng Wisata Batik Pesindon as a good tourist attraction in Pekalongan City. The type of research used is descriptive with qualitative approach. The method of analysis used in this study is SWOT analysis. Then SWOT Matrix is formulated to obtain the strategy to develop KWBP. The result shows several development strategies in the category of human resources, product and marketing.